The association between serum total folic acid concentration and severe difficulty falling asleep in US adults: NHANES 2005–2008 - An, Haoyu; Xue, Qiyun; Zhang, Jingyi (Frontiers in Neurology, 2023)
Objective The present study aimed to explore the correlation of serum total folic acid concentration with severe difficulty falling asleep among US adults. Methods Cross-sectional data were collected from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2006 and 2007 to 2008 cycles. Participants were divided into the severe difficulty falling asleep (SDFA) group and the control group according to the monthly frequency of having difficulty falling asleep. Serum total folic acid was taken as independent and dependent variables, respectively. The correlation of serum total folic acid concentration with severe difficulty falling asleep was examined using multivariable logistic regression models, where the adjusted odds ratio (OR) and 95% confidential intervals (CIs) were calculated. Results Overall, 8,926 individuals from the NHANES 2005 to 2006 and 2007 to 2008 waves were included in the analysis, of whom 683 participants had severe difficulty falling asleep. Higher serum total folic acid concentration (ng/ml) was associated with lower odds of severe difficulty falling asleep after adjusting for potentially confounding factors (OR = 0.98; 95% CI: 0.97–1.00), while participants at the highest quartile had the least odds of severe difficulty falling asleep (OR = 0.55; 95% CI: 0.40–0.74). The subgroup analysis based on gender, smoking history, and diabetes showed that this negative correlation was more significant in males, smokers, and nondiabetic population after adjusting for confounding factors. Conclusion High levels of serum folic acid were significantly related to less odds of severe difficulty in falling asleep among US adults, suggesting that folic acid supplementation may be beneficial to the prevention and even treatment of severe difficulty falling asleep.